Functional characterisation of ScIRT1 and ScIREG2 transport proteins in the nickel hyperaccumulator, Senecio coronatus - van der Pas, Llewelyn (Department of Molecular and Cell Biology, 2020)
Nickel hyperaccumulation is a unique plant adaption that has led to roughly 390 plant taxa being able to not only withstand the toxicity associated with Ni but actively translocate it to aerial tissues. However, the underlining molecular mechanisms that drive Ni hyperaccumulation remain unclear. Senecio coronatus, a Ni hyperaccumulator, is a novel species as both hyperaccumulating and non-accumulating populations can be found on the serpentine soils of the Barberton Greenstone Belt, South Africa. A comparative RNA-seq analysis on these populations of S. coronatus revealed that ScIRT1 and ScIREG2 , putative homologues of the Arabidopsis transporters, AtIRT1 and AtIREG2 which are capable of transporting Ni, showed much higher expression in the hyperaccumulating populations compared to the non-hyperaccumulating populations, suggesting a potential role in Ni hyperaccumulation. It was thus necessary to investigate whether ScIRT1 and ScIREG2 encode functional homologues of these Arabidopsis transporters. To accomplish this, irt1 and ireg2 mutants were obtained from a T-DNA insertion seed collection and their homozygosity was then determined by PCR genotyping. Since a lack of iron induces IRT1 and IREG2 expression, loss of gene expression of homozygous irt1 and ireg2 mutants by means of reverse transcriptase PCR on plant roots grown hydroponically in the absence of Fe was then done to establish full knock-out status. From this, homozygous mutants were identified, however, absence of gene expression for irt1 and ireg2 mutants was not clear. In addition to validating homozygosity, phenotypic characterisation, with the aim of developing reliable assays to be used in complementation analysis, was done by growing homozygous mutants and Col-0 in hydroponic media deficient in Fe and supplemented with Ni. The assays revealed that under Fe-deficient and Ni-supplemented conditions, a reduction in root biomass was a more reliable phenotypic characteristic for ireg2 mutants than root length or shoot biomass. In contrast, for irt1, no observable phenotype was established under Fe-deficiency conditions. In parallel, Gateway cloning was employed to create expression clones where ScIRT1 and ScIREG2 protein coding expression was to be driven by native Arabidopsis promoters pAtIRT1 and pAtIREG2 (i.e. pAtIRT1:ScIRT1 and pAtIREG2:ScIREG2) respectively for complementation of the Arabidopsis irt1 and ireg2 mutants. The open reading frames of the S. coronatus genes and the Arabidopsis promoters were PCR amplified, cloned into appropriate pDONR221 vectors, and sequence verified. The ScIREG2 clone however, revealed point mutations and could not be used. pAtIRT1 was successfully recombined with ScIRT1 to generate a two-fragment expression clone which was verified by DNA sequencing. Thus herein, the foundations for ScIRT1 and ScIREG2 complementation experiments have been established.